FOUR-STROKE MOTORCYCLE EXHAUST MANIFOLD MODIFICATION USING VARIATIONS IN THE LOCATION OF THE TEC INLET AND OUTLET DUCTS - Putro, Sartono; Subagja, Rizki (Prosiding University Research Colloquium, 2024)
This research was conducted to determine the effect of exhaust manifold modifications on motorcycle performance using torque expansion chamber (TEC) variations in the location of the inlet and outlet ducts. The test was carried out by changing the position of the TEC inlet and outlet ducts in three variations. Testing using a dynotest and a Honda Supra X 125 motorcycle. The test results show that the highest results were obtained when using variation 2. The torque obtained was 9.69 Nm at an engine rotation of 4500 rpm, the power produced was 7.53 HP at an engine rotation of 6250 rpm, and the specific fuel consumsion (sfc) produced was 0.153 kg/hour. HP at 6250 rpm.